The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s10863-008-9130-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mitochondrial DNA level on cellular energy metabolism: implications for mitochondrial diseases

Abstract: The total amount of cellular mitochondrial DNA (mtDNA) varies widely and seems to be related to the nature and metabolic state of tissues and cells in culture. It is not known, however, whether this variation has any significance in vivo, and to which extent it regulates energy production. To better understand the importance of the cellular mtDNA level, we studied the influence of a gradual reduction of mtDNA copy number on oxidative phosphorylation in two models: (a) a control human cell line treated with dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 35 publications
3
28
0
Order By: Relevance
“…Rocher et al . 60 indicated that the quantity of mtDNA in human cell lines is tightly correlated to CIV activity. Importantly, apparent excess of catalytic capacity does not signify that it is not functionally required, considering the importance for high affinity of mitochondria to oxygen 55, 61 and the role of CIV in the control of cytochrome reduction levels 62 .…”
Section: Discussionmentioning
confidence: 99%
“…Rocher et al . 60 indicated that the quantity of mtDNA in human cell lines is tightly correlated to CIV activity. Importantly, apparent excess of catalytic capacity does not signify that it is not functionally required, considering the importance for high affinity of mitochondria to oxygen 55, 61 and the role of CIV in the control of cytochrome reduction levels 62 .…”
Section: Discussionmentioning
confidence: 99%
“…These characteristics are compatible with the shift from hypoxia to anoxia, where mitochondria switch from producers to consumers of ATP without changing their mitochondrial mass 54 . Moreover, the mtDNA content and mtRNA levels decrease when mitochondria cease their energy production 55 . Taken together, these data indicate that day 4-anoxia-treated satellite cells display the hallmarks of anoxic mitochondria, and suggest that day 4 post mortem satellite cells might not be in an truly anoxic microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…In essence, the reduction state of the inner membrane is the signal giver and output sensor for the reactive (as opposed to proactive) expression of mitochondrial genes. Certainly, translational regulation, protein stability, phosphorylation and supercomplex assembly all modulate respiratory rate; but these mechanisms ultimately revolve around transcriptional control, as demonstrated by the near-linear correlation between mtDNA copy number and respiratory rate [35]. This system enables respiratory stoichiometry to be calibrated locally to need, tailoring supply to demand.…”
Section: Pr Ospects and Overviews N Lanementioning
confidence: 99%